Facing the Music or Burying Our Heads in the Sand?: Adaptive Emotion Regulation in Midlife and Late Life - Waldinger, Robert J. (2010)
Defenses that keep threatening information out of awareness are posited to reduce anxiety at the cost of longer-term dysfunction. By contrast, socioemotional selectivity theory suggests that preference for positively-valenced information is a late-life manifestation of adaptive emotion regulation. Using longitudinal data on 61 men, we examined links between emotion regulation indices informed by these distinct conceptualizations: defenses in earlier adulthood and selective memory for positively-valenced images in late-life. Use of avoidant defenses in midlife predicted poorer memory for positive, negative, and neutral images nearly 4 decades later. Late-life satisfaction was positively linked with midlife engaging defenses but negatively linked at the trend level with concurrent positive memory bias.